Pengolahan Limbah Ampas Tahu menjadi Tepung oleh Kelompok Karang Taruna Kelurahan Balangnipa - Ishak, A. Taufik; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar; Jafar, Muhammad; Sukmawati, Sukmawati; Nurdin, Nurdin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Industrial by-products are industrial waste, which are produced during the production process of an industry but are not the desired main product. Components or materials that arise as a natural result of industrial processes and often have no commercial value or can even be considered waste. One of the industrial waste products is tofu dregs. Tofu dregs waste is a by-product of the process of making soybean tofu products. When soybeans are processed to produce tofu, the soybean seeds are soaked, ground, and extracted to obtain soy milk. This soy milk is then processed into tofu, while the tofu dregs become waste. Balangnipa sub-district has 4 tofu industries operating which produce tofu dregs waste which is only made or used as animal feed even though tofu dregs waste can be made into a product in the form of flour. The lack of public knowledge regarding processing of tofu dregs waste is the basis for this service. So that this service will help the community in implementing flour making through the stages of counseling, training and mentoring to Karang Taruna Group partners. The results of this program are able to increase partners' knowledge in processing tofu dregs waste into flour. The results of this program are able to increase partners' knowledge and productivity in processing tofu dregs waste into flour. The resulting product is packaged in a 500 gram pouch.